Narrating Everyday Precarity: Women’s Voices from Resource Poor Areas - Masenya, Veronica; de Wet, Katinka; Coetzee, Jan K. (Qualitative Sociology Review, 2017)
African family life in South Africa’s post-apartheid context is shaped by the socio-political history of the country. Despite various attempts to address the remnants of poverty, unequal distribution of resources and the lack of livelihood services still exist. African families from resource poor areas of townships in South Africa are still faced with poverty and deprivation. Black African women, often with minimum schooling, suffer the most from these scourges. This article aims to explore the everyday life narratives of precarity at various levels and the manner in which women from Mangaung Township in Bloemfontein cope with this. They talk about the fragile relationships within the family, about the gendered dynamics of the household, and about the importance of support networks.